PENGUATAN PROFIL PELAJAR PANCASILA ASPEK BERKHEBINEKAAN GLOBAL PADA PELAJARAN IPAS MATERI KEKAYAAN BUDAYA INDONESIA DI KELAS IV SDN PETERONGAN: PENGUATAN PROFIL PELAJAR PANCASILA ASPEK BERKHEBINEKAAN GLOBAL PADA PELAJARAN IPAS MATERI KEKAYAAN BUDAYA INDONESIA DI KELAS IV SDN PETERONGAN - Indriya Mella Agustina; Duwi Nuvitalia; Ikha Listyarini; Arfanny Hanum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyze the strengthening of the profile of Pancasila students in aspects of global diversity in science lessons on Indonesian cultural richness in class IV SDN Peterongan. The type of research used is descriptive qualitative. Collecting data in this study using observation, interviews, and documentation. The data analysis technique used is Data reduction, DataDisplay, dan Verifikasi Conclusions Drowing. The results showed that grade IV students at SDN Peterongan have shown the strengthening of the Pancasila Student Profile in the aspect of Global Service in science lessons on Indonesian Cultural Property material that has been applied in the school environment in accordance with 3 elements, namely recognizing and respecting culture; intercultural communication skills in interacting with others; and reflection and responsibility for the experience of diversity. Thus, it can be concluded that strengthening the profile of Pancasila students in aspects of global khebinekaan in science lessons on Indonesian cultural property material in grade IV SDN Peterongan has been implemented in learning.